Effects of different ages on frozen semen quality and in vitro fertilization efficiency in Wannan black pigs - Xu, Changzhi; Yang, Xianshu; Sui, Heming; Tong, Xu; Zhang, Dandan; Zheng, Xianrui; Jiao, Jun; Wang, Chonglong; Cao, Zubing; Zhang, Yunhai (Frontiers in Veterinary Science, 2024)
According to previous studies, the quality and fertilization rate of fresh sperm from boars of different ages were significantly different. However, the difference of freeze–thaw sperm quality and fertility in boars of different ages is unclear. In this study, boars of a Chinese native breed were assigned into two groups. Each group consisted of five boars aged aged either 2–3 years (young boars = YB) or 5–6 years (aging boars = AB) A total of 60 ejaculates for each group were collected and cryopreserved. Semen quality and in vitro fertility of post-thaw sperm was evaluated. The results showed that the concentration and motility of fresh sperm collected from AB were similar to YB, but their semen volume was higher than that in YB (p < 0.05). Frozen–thawed sperm of AB had lower viability than YB, and higher abnormal rate and reactive oxygen species (ROS) levels of YB (p < 0.05). There was no effect of the age on post-thaw sperm motility and time survival. Functional assessments indicated that increasing age markedly compromises the integrity of the sperm plasma membrane and acrosome, as well as mitochondrial functionality post-thaw, albeit without affecting DNA integrity. Furthermore, increasing age of boars reduces the ability of sperm to bind to the oocyte zona pellucida after thawing, delaying the time of the first embryo cleavage after fertilization. Finally, the early developmental efficiency of in vitro fertilized embryos progressing from 4-cell to blastocyst derived from post-thaw sperm in AB significantly decreased compared to those from YB (p < 0.05). Taken together, these results suggest that increasing age in boars impairs the quality and in vitro fertility of frozen thawed sperm.